A Discursive Approach to Recognition in the Practicum - Balslev, Kristine; Vanhulle, Sabine; Tominska, Edyta (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
This article is part of a larger research project on professional development, and more specifically the emergence of “professional knowledge” among pre-service teachers. The intent here is to analyze recognition phenomena in supervisory discussions. We consider recognition of pre-service teachers’ discourse as a condition for the emergence of professional knowledge. What “recognition markers” do evaluators seize from this discourse to decode its content and meaning, to adjust and influence it? How do these markers contribute (or fail to contribute) to establishing “shared communicative spaces”? Our analyses show that the emergence of these shared communicative spaces involves tensions that reveal (or fail to reveal) forms of recognition. These forms of recognition affect the shaping of pre-service teachers’ professional knowledge, as well as components of pre-service teachers’ identity that also influence the elaboration of professional knowledge.